Pembelajaran Kooperatif Mampu Merubah Tingkat Pemahaman Peserta Didik Pada Proses Pembelajaran Matematika. - Asri Ode Samura (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2016)
Cooperative learning one learning model that can suss out the problems in learning process in class. suitable mathematical logic taught using cooperative learning model. Cooperative learning are interdependent positively (Positive Interdependence), Direct interaction (Face-to-Face Interaction), responsibility of individuals and groups ( Individual & Group Accountability ), interpersonal skills and small-group Skills), and the process of  group work (group processing).Cooperative has also an effect in the learning process. Learning in class by using the cooperative model is very effective, it can quickly and easily make students understand the material being taught.